Metabolic engineering of microorganisms for the production of multifunctional non‐protein amino acids: γ‐aminobutyric acid and δ‐aminolevulinic acid. Issue 6 (6th March 2021) - Su, Anping; Yu, Qijun; Luo, Ying; Yang, Jinshui; Wang, Entao; Yuan, Hongli
Summary: Gamma‐aminobutyric acid (GABA) and delta‐aminolevulinic acid (ALA), playing important roles in agriculture, medicine and other fields, are multifunctional non‐protein amino acids with similar and comparable properties and biosynthesis pathways. Recently, microbial synthesis has become an inevitable trend to produce GABA and ALA due to its green and sustainable characteristics. In addition, the development of metabolic engineering and synthetic biology has continuously accelerated and increased the GABA and ALA yield in microorganisms. Here, focusing on the current trends in metabolic engineering strategies for microbial synthesis of GABA and ALA, we analysed and compared the efficiency of various metabolic strategies in detail. Moreover, we provide the insights to meet challenges of realizing industrially competitive strains and highlight the future perspectives of GABA and ALA production. Abstract : For the first time, we put GABA and ALA together for a detailed summary, analysis and comparison, and put forward further strategies to meet the challenges of industrial competition strains.